Hawaii's People Third Edition - Lind, Andrew W. (University of Hawaii Press, 2021)
Hawaii's experiences in race relations are a constant source of fascination both to students of the subject and to laymen. During the last hundred years, some 400,000 Chinese, Japanese, Portuguese, Koreans, Filipinos, and Caucasians have come to Hawaii, most of them as laborers for sugar and pineapple plantations. Contrary to popular impressions, the Island pattern of social organization is by no means a simple one. The plantation, as well as commercial, military, and tourist institutions and values, have all influenced one another and the Island social pattern.Hawaii's People is the story of how the many diverse ethnic and racial groups in Hawaii are gradually becoming one people. Fortunately, Hawaii possesses over a century of accurate statistical data showing what has happened during the period of racial contact and association. The author has drawn heavily on this material for his book and has included in the 3rd edition the results of the 1960 U.S. Census.Hawaii's People, written for the layman as well as the sociologist, is a non-technical, informative account of who Hawaii's people are, where they came from, why and when they came, where and how they live, and-most interesting of all-what they are becoming. The text is supplemented by 28 tables, 2 charts, and 2 maps
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2021)
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social